Brain network of athletes in motor imagery and action anticipation: an ALE meta-analysis and MACM analysis - Wang, Yanqiu; Sun, Yang; Yu, Jiangsheng; Cheng, Xiaorong; Niu, Zhebin (Frontiers in Sports and Active Living, 2025)
Understanding how athletes mentally simulate and anticipate actions provides key insights into experience-driven brain plasticity. While previous studies have investigated motor imagery and action anticipation separately, little is known about how their underlying neural mechanisms converge or diverge in expert performers. This study conducted a meta-analysis using activation likelihood estimation (ALE) and meta-analytic connectivity modeling (MACM) to compare brain activation patterns between athletes and non-athletes across both tasks. We systematically reviewed functional magnetic resonance imaging studies and included 20 eligible studies. ALE was used to identify consistent activation patterns, followed by contrast and conjunction analyses. MACM was used to further explored connectivity among key brain regions. Results showed that athletes exhibited stronger activation in the left middle and precentral gyrus during motor imagery, and in the superior frontal gyrus, bilateral precentral gyrus, and right middle frontal gyrus during action anticipation. Non-athletes showed greater activation in visual regions such as the middle occipital gyrus. Connectivity analyses revealed that athletes formed a cohesive fronto-parietal-temporal network integrating motor imagery and action prediction, which was not observed in non-athletes. These findings highlight a nested and efficient action observation network in athletes, supporting the integration of internally generated and externally guided action processes. This work advances models of perceptual-motor expertise and provides insight into how long-term sports training modulates brain plasticity.